2019
DOI: 10.1101/753145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrophysiological network alterations in adults with copy number variants associated with high neurodevelopmental risk

Abstract: Rare copy number variants associated with increased risk for neurodevelopmental and psychiatric disorders (referred to as ND-CNVs) are characterized by heterogeneous phenotypes thought to share a considerable degree of overlap. Altered neural integration has often been linked to psychopathology and is a candidate marker for potential convergent mechanisms through which ND-CNVs modify risk; however, the rarity of ND-CNVs means that few studies have assessed their neural correlates. Here, we used magnetoencephal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Despite the proposed neuronal integration deficits in 22q11.2DS and other neurodevelopmental CNVs, there have been relatively few studies of cortical oscillations in these high-risk groups. In a recent resting- state MEG study in adult CNV carriers, we found common patterns of oscillatory dysconnectivity across nine different neurodevelopmental CNV loci, including 22q11.2DS, suggesting a putative mechanism by which neurodevelopmental CNVs could increase risk of psychopathology (41). Due to the relatively small numbers of participants with each CNV, it was not possible to explore the associations between oscillatory activity and neurodevelopmental symptoms or psychopathology.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Despite the proposed neuronal integration deficits in 22q11.2DS and other neurodevelopmental CNVs, there have been relatively few studies of cortical oscillations in these high-risk groups. In a recent resting- state MEG study in adult CNV carriers, we found common patterns of oscillatory dysconnectivity across nine different neurodevelopmental CNV loci, including 22q11.2DS, suggesting a putative mechanism by which neurodevelopmental CNVs could increase risk of psychopathology (41). Due to the relatively small numbers of participants with each CNV, it was not possible to explore the associations between oscillatory activity and neurodevelopmental symptoms or psychopathology.…”
Section: Introductionmentioning
confidence: 83%
“…The functional connectivity changes we found in children are similar to those previously reported by our research group in adult neurodevelopmental CNV carriers. (41). While there were relatively few participants with 22q11.2DS in that study (n=14), analysis of the 22q11.2 group alone found similar connectivity reductions as the cross-CNV analysis but in addition, a number of nodes with hyperconnectivity were identified.…”
Section: Discussionmentioning
confidence: 99%
“…While it is interesting that MRVE correlation has shown promise as a measure of functional connectivity, the true test of its usefulness will be its performance in patient groups. Neural variability measures such as Multi-scale Entropy (MSE) ( Bosl, Tierney, Tager-flusberg, Nelson, 2011 , Costa, Goldberger, Peng, 2005 , Ghanbari, Bloy, Edgar, Blaskey, Verma, Roberts, 2015 , Mizuno, Takahashi, Cho, Kikuchi, Murata, Takahashi, Wada, 2010 ), and AEC connectivity ( Andreou, Nolte, Leicht, Polomac, Hanganu-opatz, Lambert, Engel, Mulert, 2015 , Dima, Adams, Linden, Baird, Smith, Foley, Perry, Routley, Magazzini, Drakesmith, Williams, Doherty, van den Bree, Owen, Hall, Linden, Singh, 2020 , Koelewijn, Hamandi, Brindley, Brookes, Routley, Muthukumaraswamy, Williams, Thomas, Kirby, te Water Naudé, Gibbon, Singh, 2015 , Koelewijn, Lancaster, Linden, Dima, Bethany, Magazzini, Barawi, Brindley, Adams, Tansey, Bompas, Tales, Bayer, Singh, 2019 ) have both been shown to be able to distinguish patient groups from controls. Future work will investigate whether MRVE correlation can provide understanding about connectivity changes associated with disease, in comparison to conventional measures based on the oscillatory components of brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also explored similarities in functional connectivity patterns across CNVs. A magnetoencephalography study investigated resting-state oscillatory connectivity and reported decreased connectivity between occipital, temporal, and parietal areas in CNV carriers (64). Moreau et al (65) combined functional MRI data from 16p11.2 and 22q11.2 CNV carriers; individuals with idiopathic ASD, schizophrenia, and attention-deficit/hyperactivity disorder; and respective control subjects to look for convergent patterns of functional connectivity alterations.…”
Section: Convergence In Neurodevelopmental Cnvsmentioning
confidence: 99%